Molecular and Pathological Investigations of Selected Viral Neuropathogens in Rabies-Negative Brains of Cats and Dogs Revealed Neurotropism of Carnivore Protoparvovirus-1 - Wardhani, Sabrina Wahyu; Wongsakul, Boonyakorn; Kasantikul, Tanit; Piewbang, Chutchai; Techangamsuwan, Somporn (Frontiers in Veterinary Science, 2021)
Throughout the year, the Thai Red Cross Society (TRCS), Bangkok, Thailand, received more than 100 animals that died of suspected rabies due to neurological clinical signs. Concerning the role of viral infection in the brain in the outcome of neurological diseases in cats and dogs, a comprehensive study was conducted of 107 brain samples of cats and dogs submitted to the TRCS from August 2019 to August 2020. Selective molecular screening using conventional polymerase chain reaction (PCR) and reverse transcription PCR targeting nine viral pathogens was employed in addition to histopathological investigations. The results showed that carnivore protoparvovirus-1 (CPPV-1) was detected in 18.69% of the cats and dogs sampled (20/107). These results were found in young and old animals; the brain tissue did not show any pathological changes suggesting encephalitis or cerebellar hypoplasia. In addition, feline calicivirus, feline alphaherpesvirus-1, feline coronavirus, and canine distemper virus were also detected, providing a broader range of potential viral infections to consider in the clinical manifestation of neurological disorders in companion animals. The detection of all pathogens was confirmed by the localization of each viral antigen in various resident brain cells using immunohistochemistry. A unique L582S amino acid substitution of the non-structural protein 1 gene coding sequence, speculated to be associated with the neurotropism of CPPV-1 in cats and dogs, was not evident. In conclusion, this study revealed a noteworthy neurotropism of CPPV-1 in both cats and dogs without neurological lesions.